Viruses : from understanding to investigation - Payne, Susan (Academic Press, an imprint of Elsevier, 2017)
Viruses: From Understanding to Investigation provides students with a map for lifetime learning by presenting the definition and unique characteristics of viruses, including major topics, such as the virus lifecycle, structure, taxonomy, evolution, history, host-virus interactions and methods to study viruses. In addition, the book assesses the connections between, and among, the aforementioned topics, providing an integrated approach and in-depth understanding of how viruses work.